Cure monitoring and structural health monitoring of composites using micro-braided distributed optical fibre. (15th December 2020) - Rufai, Olubukola; Chandarana, Neha; Gautam, Mayank; Potluri, Prasad; Gresil, Matthieu
Abstract: In this paper, cure monitoring of a composite laminate is conducted, followed by subsequent structural health monitoring (SHM). A distributed optical fibre (DOF) sensor was embedded between glass fibre fabric plies during manufacture; part of the DOF length was micro-braided using glass fibres, while the remaining length was left 'bare' (as-received condition). In situ and real-time strain measurement during the infusion and curing processes of the laminate was completed. Cure monitoring of composite materials using different fibre orientations, sensor locations, raw materials, and manufacturing methods has been widely studied. However, no consensus was reached due to differences in raw materials, temperature profile, manufacturing method, fibre orientation, and sensor location. The manufactured composite plate was then subjected to repeated loading during a quasi-static four-point bending test, and the strain development along the length of the DOF was recorded. Comparable results were obtained from the micro-braided and bare sections of the DOF, showing the suitability of micro-braided optical fibres for real-time strain monitoring in composite structures. The micro-braiding DOF facilitates handling for automated manufacturing methods and can be used to follow the full life cycle of a composite from fabrication till end-of-life.